QUALITY OF LIFE IN PATIENTS WITH LARYNGEAL AND LARYNGOPHARYNGEAL CANCER IN SHORT-AND LONG-TERM FOLLOW-UP - S. Yu. Chizhevskaya; Е. L. Choinzonov; L. N. Balatskaya (Сибирский онкологический журнал)
The study included 96 patients with morphologically verified  squamous cell carcinoma of larynx and laryngopharynx T2–4N0–2M0 stage of the tumor process who were administered two courses of neoadjuvant chemotherapy at 3–4 weeks interval by the scheme paclitaxel 175 mg/m2, carboplatin AUC-6 plus radiotherapy in the regimen of multifractionated radiation dose of 1.3 Gy twice a day at 4 hours interval. In case of complete regression of the tumor (n=33) radiotherapy was performed to the accumulated radical dose of 65 isoGy. The next stage in partial regression and stabilization of the process (n=63) was radical surgical intervention. EORTC QLQ-30 and QLQ – H&N35 questionnaires were used to estimate quality of life of the patients. Quality of life as a criterion for the assessment of treatment efficacy was correlated with a significant increase in the 2-year overall and disease-free survival in patients who received chemoradiotherapy compared to those who underwent combined modality treatment including surgery. Changes in the values of EORTC QLQ-30 and QLQ – H & N35 modules clearly indicate the relationship between the quality of life measures and treatment methods.